Seronegative Arthritis as a Complication of Whipple's Disease. Issue 14 (May 2021) - DeBoer, Rebecca; Jayatilaka, Sahani; Donato, Anthony
Whipple's disease (WD) is an uncommon cause of seronegative arthritis. WD is known for its gastrointestinal symptoms of diarrhea, weight loss, and abdominal pain. However, arthritis may precede gastrointestinal symptoms by 6 to 7 years. We describe a case of an 85-year-old Caucasian male with multiple joint complaints, not responsive to traditional treatments for conditions such as rheumatoid arthritis and osteoarthritis. We suggest that WD be considered for seronegative arthritis especially affecting large joints.